Soft Robotics: Flexible and Stretchable Strain Sensing Actuator for Wearable Soft Robotic Applications (Adv. Mater. Technol. 3/2016). Issue 3 (15th June 2016) - Yeo, Joo Chuan; Yap, Hong Kai; Xi, Wang; Wang, Zhiping; Yeow, Chen‐Hua; Lim, Chwee Teck
Abstract : In article number 1600018, Chen Hua Yeow, Chwee Teck Lim, and co‐workers present a strain sensing actuator for soft robotics applications. The sensing actuator comprises a highly stretchable and robust silver microstructured mesh network as the sensing element. It can be embedded in a glove for wearable rehabilitation application by sensing the extent of actuation.